Computational Investigation of a Wind Turbine Shrouded with a Circular Ring - Takey, Mohamed; Mat Lazim, Tholudin; Ishak, Iskandar Shah; Nik Mohd, N.A.R; Othman, Norazila (CFD Letters, 2020)
In this research work, a new design concept for shrouded turbines is introduced using a circular flange ring instead of a diffuser. The performance of a wind turbine shrouded with the conventional configuration of flanged diffusers is firstly investigated. This allows comparison to be made with the performance of the new design proposed in this project. The bare turbine used in this research work is a horizontal axis wind turbine with a diameter of 0.6 m, and the flange height is 10% of the diameter. The performance of the shrouded turbine is investigated using computational fluid dynamics; by solving the flow field using three-dimensional Reynolds Averaged Navier-Stokes for incompressible flow. Findings indicate that the performance of the turbine shrouded with the flange ring is superior to the bare turbine by 33%. It also has benefit over the conventional design as this new design concept is simpler and uses lesser material since it is not using the diffuser, which favorably in turn will reduce the cost. Subsequently, the findings of this research may have the potential to expedite the developments of green-source energy that undoubtedly could benefit the entire growing wind turbine industry.